KARAKTERISTIK DAN KEBUTUHAN ANAK BERKEBUTUHAN KHUSUS - Khairun Nisa; Sambira Mambela; Luthfi Isni Badiah (Jurnal Abadimas Adi Buana, 2018)
Children with special needs (ABK) are children who grow and develop with various differences with children in general. The term of children with special needs does not refer to the designation for children with disabilities, but refers to the special services that children with special needs need. There are various types of categories within the scope of the term of children with special needs. In the context of special education in Indonesia, children with special needs are categorized in terms of children with visual impairment, deaf children, children with intelectual disability, children with motoric disabilities, children with social emotional disorder, and children with intelligent and special talents. Each child with special needs has different characteristics from one to another. Moreover, each child with special needs also needs special services tailored to their abilities and characteristics. It is necessary to carry out identification and assessment activities to identify their characteristics and needs. It is considered important to get the right service according to the characteristics, needs and abilities.